EVALUASI KEBIJAKAN KURIKULUM MERDEKA BELAJAR DI SMK NEGERI 3 PANDEGLANG - Surnata; Sonjaya, Trisna (NIAGARA Scientific Journal, 2025)
ABSTRACT Curriculum is the main key to success in learning. So in order to achieve this success, an evaluation needs to be carried out to improve and analyze the implementation of the curriculum, to be used as a consideration used to make a decision. In this study, the researcher examines the evaluation of the Merdeka curriculum implementation policy. This study was conducted to examine and evaluate the implementation of the Merdeka curriculum program at SMK Negeri 3 Pandeglang using the CIPP (Context, Input, Process, and Product) evaluation model. The data sources obtained were obtained from interviews, observations and documentation conducted with the Principal, Teachers, TU, Committee Chair, Parents and Students. The results of the interviews obtained will then be analyzed by conducting qualitative descriptive analysis. The conclusion obtained from this study is that the implementation of the Merdeka curriculum program applied at SMK Negeri 3 Pandeglang was carried out in stages well, although it was constrained by several obstacles including in conducting assessments and teacher training which was still lacking. Keywords: Policy Evaluation, Merdeka Curriculum, CIPP